2013
DOI: 10.1161/circresaha.111.300483
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Prevents Progression of Experimental Pulmonary Hypertension via Inhibition of Autophagy and Lysosomal Bone Morphogenetic Protein Type II Receptor Degradation

Abstract: P ulmonary arterial hypertension (PAH) is a progressive disease characterized by a marked increase in pulmonary arterial pressure and right ventricular hypertrophy (RV/LV+Sep). 1 The increase in pulmonary vascular resistance is due to adventitial, medial, and intimal thickening of small pulmonary arteries, resulting from fibroblast, smooth muscle, and endothelial cell proliferation.2 Increased proliferation of pulmonary arterial smooth muscle cells (PASMCs) and resistance to apoptosis is a central feature of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(231 citation statements)
references
References 43 publications
(52 reference statements)
13
214
2
2
Order By: Relevance
“…Therefore, our next objective was to investigate whether autophagy was activated as a survival mechanism or, in opposition, was induced to produce cell death. To address this question, we used two modulators of autophagy known for their effects in the final steps in the process of autophagy: STF-62247 as an activator (Anbalagan et al, 2012) and chloroquine as an inhibitor (Long et al, 2013) of autophagy. We used rapamycin as an mTOR inhibitor (Zhou et al, 2010), and 3-MA as a PI3K class III inhibitor (O'Farrell et al, 2013), to modulate two proteins considered the major regulators of this process (Jung et al, 2010;O'Farrell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our next objective was to investigate whether autophagy was activated as a survival mechanism or, in opposition, was induced to produce cell death. To address this question, we used two modulators of autophagy known for their effects in the final steps in the process of autophagy: STF-62247 as an activator (Anbalagan et al, 2012) and chloroquine as an inhibitor (Long et al, 2013) of autophagy. We used rapamycin as an mTOR inhibitor (Zhou et al, 2010), and 3-MA as a PI3K class III inhibitor (O'Farrell et al, 2013), to modulate two proteins considered the major regulators of this process (Jung et al, 2010;O'Farrell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…3-MA is an inhibitor of PI3K class III (O'Farrell et al, 2013). Chloroquine inhibits autophagy because it raises the lysosomal pH, which leads to inhibition of both fusion of the autophagosome with the lysosome and lysosomal protein degradation (Long et al, 2013). Samples resuspended in INRA96 ® were stored at 4°C for 5 days (0, 24, 48, 72, 96 h).…”
Section: Incubation Mediamentioning
confidence: 99%
“…BMPR-II agonists and drugs that non-specifically enhance BMP signalling have shown beneficial effects in experimental PH [24,[28][29][30][31]. In cultured ECs, BMP9 was shown to increase BMPR-II signalling, prevent apoptosis, decrease angiogenic behaviour and promote monolayer integrity [31].…”
Section: Tgf-β Signallingmentioning
confidence: 99%
“…This dose of CQ was chosen based on the investigation by Long et al 15 who observed beneficial effects on indices of pulmonary hypertension at 25 and 50 mg/kg/day. To investigate the therapeutic potential of CQ to inhibit TLR signaling proteins in hypertension, adult (12 week old) SHR (Veh n = 13; CQ n = 13) and WKY (Veh n = 11; CQ n = 11) rats, as well as a group of young (5 week old) SHR (Veh n = 6; CQ n = 6), were killed at the conclusion of the 21-day treatment and mesenteric resistance arteries (MRA) were harvested (this is referred to as study A).…”
Section: Treatmentmentioning
confidence: 99%